Isaiah 40-66 a commentary - Westermann, Claus; Stalker, David M.G. (London, UK SCM, 1969)
Includes bibliographical references.
Originally published as "Das Buch Jesaia, 40-66" [Das Alte Testement Deutsch 19], Gottingen, Vandenhoeck adn Ruprecht, 1966.
Keywords: Bible. O.T. Isaiah XL-LXVI -- commentaries